School Library Administration Management Towards a Literacy-Based Educational Learning Center for Elementary School Students - St. Marwiyah; Alauddin; Hakim Yasin (Program Studi PGSD Universitas Madako Tolitoli, 2025)
This study reviews the strategy of transforming school libraries into learning centers that focus on educational literacy, taking into account the effectiveness of managerial supervision in supporting these changes. This study aims to examine the transformation of school libraries into educational literacy-based learning centers through an analysis of the effectiveness of library administrative mengement at Integrated Islamic Elementary School, Palopo City. Qualitative methods are the focus of analysis of research findings through the application of ethnographic approaches. The subject of this study was the library manager. Data collection techniques by conducting observation activities as well as interviews with respondents to collect information or data to support data analysis. The results of the confirmed analysis of the progressivity of the administrative management of school library services showed a percentage increase of all observed sub-indicators. From the results of this study, it can be seen that the transformation of school library services has increased significantly from the comparison of the 2023-2024 period. The implication of this study is the importance of strengthening the role of school library operators in effectively and consistently managing all sub-sectors of the transformative library administration service arrangement.